Clinical spectrum and genotype-phenotype correlations in PRRT2 Italian patients. (September 2020) - Balagura, Ganna; Riva, Antonella; Marchese, Francesca; Iacomino, Michele; Madia, Francesca; Giacomini, Thea; Mancardi, Maria Margherita; Amadori, Elisabetta; Vari, Maria Stella; Salpietro, Vincenzo; Russo, Angelo; Messana, Tullio; et al.
Abstract: Prrt2 is a neuron-specific protein expressed at axonal and pre-synaptic domains, involved in synaptic neurotransmitter release and modulation of intrinsic excitability. Mutations in PRRT2 cause a spectrum of autosomal dominant paroxysmal neurological disorders including epilepsy, movement disorders, and hemiplegic migraine and show incomplete penetrance and variable expressivity. We assessed the diagnostic rate of PRRT2 in a cohort of Italian patients with epilepsy and/or paroxysmal kinesigenic dyskinesia (PKD) and evaluated genotype-phenotype correlations. Clinical data were collected using a structured questionnaire. Twenty-seven out of 55 (49.1%) probands carried PRRT2 heterozygous pathogenic variants, including six previously known genotypes and one novel missense mutation. A family history of epilepsy starting in the first year of life and/or PKD was strongly suggestive of a PRRT2 pathogenic variant. Epilepsy patients harbouring PRRT2 pathogenic variants showed earlier seizure onset and more frequent clusters compared with PRRT2 -negative individuals with epilepsy. Moreover, we did also identify individuals with PRRT2 pathogenic variants with atypical age at onset, i.e. childhood-onset epilepsy and infantile-onset PKD. However, the lack of a clear correlation between specific PRRT2 genotypes and clinical manifestations and the high incidence of asymptomatic carriers suggest the involvement of additional factors in modulating expressivity of PRRT2 -related disorders. Finally, our study supports the pleiotropic and multifaceted physiological role of PRRT2 gene which is emerging from experimental neuroscience. Graphical abstract: PRRT2 -associated paroxysmal disorders have a quite definite age at onset: 3–12 months for epilepsy, first decade for paroxysmal kinesigenic dyskinesia (PKD) and hemiplegic migraine. Atypical presentations (in red) can occur childhood-onset epilepsy and infantile- or adult-onset PKD. A novel missense variant c.809T>A (p.Ile270Asn) causes PKD. Image 1 Highlights: The diagnostic rate and genotype-phenotype correlation for PRRT2 were assessed in Italian patients with epilepsy or PKD. PRRT2 pathogenic variants were more associated with onset in the first year of life and a family history of epilepsy or PKD. Carriers of PRRT2 pathogenic variants displayed earlier seizure onset and more frequent seizure clusters. Incomplete penetrance and the lack of genotype-phenotype correlation suggest a complex modulation in expressivity of PRRT2 .